Anti-Corruption Programs for Governors' Campaign Period 2017-2018 in Java Island - Bramantyo, Muhammad (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2023)
Most of the studies regarding political campaigns focus heavily on strategy, evaluation, and communication by the candidate during the campaign. However, the study regarding anti-corruption programs campaigned by political candidates is still under research. This study examines the anti-corruption programs proposed by candidates for governor and vice governor on Java Island during 2017-2018 regional election. Further, this study employed a qualitative method using content analysis. The three objectives of this study are to examine the existence of anti-corruption program in vision-mission-working programs (VWMP) set by candidates, communication regarding anti-corruption programs during campaigning, and explanation of anti-corruption programs during electoral debate. The results revealed that only six of the thirteen candidates who ran for regional office included anti-corruption programmes in their VWMPs, seven candidates communicated their programs during the campaign period, and nearly all candidates explained their anti-corruption strategy in the electoral debate because the panelists asked them the question. It is argued that candidates did not prioritize campaigning for their anti-corruption programs because programs such as economic development, free education, and health care are more likely to get sympathy and support from voters